2013
DOI: 10.1038/cgt.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of C5 complement enhance vaccinia virus oncolysis

Abstract: Genetically engineered tumor-selective vaccinia virus (VV) has been demonstrated to be a highly effective oncolytic agent, but immune clearance may limit its therapeutic potential. As previously demonstrated, immunosuppression can lead to significant enhancement of viral recovery and therapeutic effect, but the magnitude of complement-mediated viral inactivation has not been fully elucidated and warrants further investigation. Using fluorescent microscopy and quantitative plaque assays, we have determined comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…For instance, intravenous or intra-arterial administration of OVs such as recombinant HSV1 leads to its rapid recognition and elimination by the circulating complement and antibodies of the humoral defense system (18, 19). This also has been shown for VV (20), NDV (21), MV (22), and Ad (23, 24). Intratumoral administration also can lead to complement- and antibody-mediated destruction of the OV.…”
Section: Innate Immunitysupporting
confidence: 70%
“…For instance, intravenous or intra-arterial administration of OVs such as recombinant HSV1 leads to its rapid recognition and elimination by the circulating complement and antibodies of the humoral defense system (18, 19). This also has been shown for VV (20), NDV (21), MV (22), and Ad (23, 24). Intratumoral administration also can lead to complement- and antibody-mediated destruction of the OV.…”
Section: Innate Immunitysupporting
confidence: 70%
“…27 A recently published study demonstrated that in immune hosts, antibody-mediated vaccinia virus neutralization is dependent on the complement system, and in both small and large immunized animals, the combination of complement inhibition with vaccinia virus treatment results in increased delivery to tumor and virus stability in the blood. 28 Ultimately, further evaluation of complement inhibition in combination with other immunotherapies such as viral oncolytic therapy will determine the ideal role for complement inhibition in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, though the inflammatory response was affected, the development of the adaptive immune response was not, as upon reinfection these differences were no longer apparent (32). Instead C5 appears to be rapidly activated independently of C3 exerting an influence over the development of the innate immune response by participating in local recruitment of neutrophils and may function independently of host Abs to induce clearance of VACV (33). Therapeutic treatment with a specially engineered C5a agonist, EP67, completely protects from lethal influenza infection (34); therefore, the rapid activation of the C5 component induced by MVA infection may go some way toward explaining the short-term protection provided by MVA.…”
Section: Discussionmentioning
confidence: 99%